A new miniaturized species of leaf chameleon, genus Brookesia, from a littoral forest fragment in eastern Madagascar - Rakotoarison, Andolalao; Hasiniaina, Alida Frankline; Glaw, Frank; Vences, Miguel (Zootaxa, 2024)
The number of species of miniaturized chameleons of the genus Brookesia, subgenus Evoluticauda, known to science has witnessed a dramatic increase over the past 15 years, due to the discovery of multiple microendemic species of very strong genetic divergence. So far, no described Evoluticauda species are known from the littoral forest of Madagascar’s east coast, one of the most threatened habitat types of the island. Here, we report on the discovery of a new species of Evoluticauda occurring in the littoral forest at Ankanin’ny Nofy, a touristic site at about sea level and close to Vohibola forest where probably the same species occurs. The new species, Brookesia nofy sp. nov., is sister to B. ramanantsoai which occurs in mid-altitude and highland forests (800–1300 m a.s.l.) at a similar latitude of eastern Madagascar, but differs from this species by an enormous genetic divergence in both mitochondrial and nuclear genes (8.1–9.4% uncorrected pairwise distance in the 16S rRNA gene, 1.8–2.5% in c-mos), a relatively shorter tail, a different arrangement of cephalic ridges, and probably smaller body size and relatively larger head. The discovery of B. nofy sp. nov. emphasizes the importance of conserving Madagascar’s last remaining fragments of littoral forest.